2000
DOI: 10.1002/etc.5620190515
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the capacity for development of atrazine tolerance in periphyton from a swedish freshwater site as determined by inhibition of photosynthesis and sulfolipid synthesis

Abstract: Abstract-Periphyton communities were established on glass disks under continuous exposure to atrazine (0.056-3.2 M, or 12-700 g/L) in a microcosm flowthrough system with water from the Göta Ä lv river in Southern Sweden. The effects of atrazine on chlorophyll a content, ash-free dry weight, algal species composition, and adenine and thymidine incorporation activity were determined after 4 weeks of continuous exposure. Tolerance of the algal community to atrazine was also determined by short-term inhibition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
2
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 32 publications
3
14
2
2
Order By: Relevance
“…For instance, microalgae cells exposed to atrazine were revealed to be less affected by additional atrazine than were previously unexposed cells. 64,65 This phenomenon was not so distinctive when samples were stored under cool conditions in the dark indicating a dependency of the effect from growth and an active photosystem during light exposure.…”
Section: Toxicity Testing Using Pam Uorometrymentioning
confidence: 97%
“…For instance, microalgae cells exposed to atrazine were revealed to be less affected by additional atrazine than were previously unexposed cells. 64,65 This phenomenon was not so distinctive when samples were stored under cool conditions in the dark indicating a dependency of the effect from growth and an active photosystem during light exposure.…”
Section: Toxicity Testing Using Pam Uorometrymentioning
confidence: 97%
“…Several authors have previously reported increased community tolerance to Irgarol in freshwater communities (8,79) and to other PS II inhibitors in both freshwater (23,40,70,92) and marine (7,80,96) communities. It should be noted, however, that the magnitudes of the PICT responses were quite small in some of these studies.…”
mentioning
confidence: 99%
“…These inhibitors replace the native plastoquinone at the Q B -binding niche in the D1 protein within PS II (29,72,86,105). This results in various toxic effects like inhibition of photosynthetic electron transport, which in turn leads to reduced ATP and NADPH production (25, 29) and oxidative stress due to the accumulation of reactive oxygen species (ROS) at PS II (29,31,85,89,91).Several authors have previously reported increased community tolerance to Irgarol in freshwater communities (8,79) and to other PS II inhibitors in both freshwater (23,40,70,92) and marine (7,80,96) communities. It should be noted, however, that the magnitudes of the PICT responses were quite small in some of these studies.…”
mentioning
confidence: 99%
“…Outre les difficultés rencontrées par les auteurs pour mettre en évidence l'acquisition de tolérance induite par un herbicide inhibiteur du Photosystème U (PS U : Gustavson & Wangberg 1995, Dahl & Blanck 1996Nystrôm et al 2000, Bérard & Benninghoff 2001, les études in situ concernant les pollutions diffuses d'origine agricole sont d'autant plus difficiles à mettre en oeuvre que ces milieux sont sujets aux variabilités d'apports en ces polluants et aux effets de dilution associés aux différents régimes dans les rivières (Jurgensen & Hoagland 1990, Lakshminarayana et al 1992). …”
Section: Applicationunclassified
“…Ainsi, Nystrôm et al (2000) ont mis en évidence pour du périphyton, une acquisition de tolérance faible pour une exposition chronique à des concentrations en atrazine comprises entre 0,056 et 0,56 uM dans des microcosmes, suivie d'une diminution de tolérance pour des concentrations en atrazine plus élevées. En conditions expérimentales (microcosmes extérieurs, phytoplancton d'eau douce) une diminution de tolérance des communautés exposées à un fongicide (prochloraze), a été observée (Bérard et al 2001a).…”
Section: Mise En éVidence De La Tolérance De La Communautéunclassified